PENGEMBANGAN MODUL PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA ILMU EKONOMI - Rahmadani, Annisa; Za'ba, Nasir; Rizka, Nelti; Saepul Anwar; Vicky Rohmatia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Critical thinking skills are very useful for students in learning economics and solving contextual problems. Most students still have not mastered this critical thinking skill because of the lack of supporting learning resources. This study aims to develop a problem-based learning module to improve students' thinking skills in Economics that is valid, practical, and effective. The module is expected to help students learn economics more independently and improve critical thinking skills. The research method used is development by following the ADDIE development model. The subjects of this study were high school students. Data collection used questionnaire, test, and documentation techniques. Data were collected using test, questionnaire, and interview techniques. Data were analyzed descriptively in categories and comparative quantitative. The results showed that the developed module was in the category of very valid (91 and 83), very practical (88), and effective (0.000 <0.050) used to teach economics.